Experimental analysis of a strong fluid–structure interaction on a soft membrane—Application to the flapping of a yacht downwind sail. (August 2018) - Deparday, Julien; Augier, Benoit; Bot, Patrick
Abstract: In the present study we investigate the flapping instability of a light, soft, highly cambered membrane subject to wind loading. An original in-situ experiment is developed where time-resolved pressures and forces are measured on a full-scale yacht downwind sail called a spinnaker. Particular features of this aero-elastic problem are that the membrane is weakly constrained – held only at three corners –, has a free leading edge, and has no proper shape in the absence of wind loading. In usual operating conditions, the soft structure is subject to a flapping instability giving rise to almost periodic folding and unfolding of the fore part of the sail, associated to strong variations of pressures and forces. This dynamic behavior is analyzed in detail and the space–time evolution of pressures on the membrane is linked to the flapping phenomenon. A peak in forces is observed when the membrane recovers its full shape. Thanks to the Bi-Orthogonal Decomposition (BOD) applied to the pressure fields, the dynamic behavior is reasonably well represented by the two first modes where mode 1 mostly carries the global aerodynamic force behavior and mode 2 mostly represents the effects of the membrane flapping. A physical mechanism of the flapping process is proposed based on the discussion of aerodynamic pressures and strains in the membrane. Highlights: In-situ time resolved measurements on a thin flexible membrane inflated by the wind. Study of a flapping instability of the weakly constrained free leading edge. Peak of load and creation of large suction when membrane recovers its full shape. Dynamics of flapping well characterized by two bi-orthogonal decomposition modes. Flapping mechanism has a constant reduced frequency. Proposed physical mechanism is based on creation and shedding of Leading Edge Vortex.